Regulasi diri dan stres akademik mahasiswa yang mengikuti pembelajaran daring di masa pandemi covid-19 - M. Fikri Yovega; Herlan Pratikto (INNER: Journal of Psychological Research, 2022)
Abstract This study aims to analyze the relationship between self-regulation and academic stress of working students participating in online learning during the Covid-19 pandemic. This research is a quantitative research with correlational type. There were 51 students who participated in this study with the criteria of having a dual role as a worker and currently participating in online learning at the Faculty of Psychology, University of 17 August 1945, Surabaya. Data were obtained using the academic stress scale and self-regulation scales which were compiled using a Likert scale model. The technique used for data analysis in this research is product moment correlation. The results obtained are that there is a significant negative relationship between self-regulation and academic stress. This can be interpreted that the higher the self-regulation of students, the lower the academic stress and conversely the lower the self-regulation of the students, the higher the level of academic stress. Keywords: Academic Stress; Self Regulation.